Distinct tribological endotypes of pathological human synovial fluid reveal characteristic biomarkers and variation in efficacy of viscosupplementation at reducing local strains in articular cartilage. Issue 4 (April 2020) - Irwin, R.M.; Feeney, E.; Secchieri, C.; Galesso, D.; Cohen, I.; Oliviero, F.; Ramonda, R.; Bonassar, L.J.
Summary: Objective: Viscosupplementation has been used for decades to treat mild to moderate osteoarthritis, yet it is unknown if the lubricating function of different pathological synovial fluids (SF) vary, or if they respond differentially to viscosupplementation. The objectives of this study were to (i) evaluate the friction coefficients and induced shear strains in articular cartilage when lubricated with pathological SF, (ii) identify the effect of hyaluronic acid (HA) supplementation on friction coefficients and shear strains, and (iii) identify SF biomarkers that correlate with lubricating function. Method: Human pathological SF was grouped by white blood cell count (inflammatory: >2000 cells/mm 3, n  = 6; non-inflammatory: <2000 cells/mm 3, n  = 6). Compositional analyses for lubricin and cytokines were performed. Friction coefficients and local tissue shear strain measurements were coupled using new, microscale rheological analyses by lubricating neonatal bovine cartilage explants with SF alone and in a 1:1 ratio with HA (Hymovis®). Results: Friction coefficients were not significantly different between the inflammatory and non-inflammatory pathologies ( p  = 0.09), and were poorly correlated with peak tissue strains at the cartilage articular surface (R 2  = 0.34). A subset of inflammatory SF samples induced higher tissue strains, and HA supplementation was most effective at lowering friction and tissue strains in this inflammatory subset. Across all pathologies there were clear relationships between polymorphonuclear neutrophil (PMN), IL-8, and lubricin concentrations with cartilage tissue strains. Conclusion: These results suggest that pathological SF is characterized by distinct tribological endotypes where SF lubricating behaviors are differentially modified by viscosupplementation and are identifiable by biomarkers.